Robert B. Parker's Fool's paradise [large type] - Lupica, Mike; Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Jesse Stone novels, 2020)
When a body is discovered at the lake in Paradise, Police Chief Jesse Stone is surprised to find he recognizes the murder victim-- he had been at the same AA meeting as Jesse the evening before. Otherwise there is no clue to the man's identity. He isn't a local, doesn't have ID on him, nor does any neighboring state have a reported missing person matching the man's description. Their single lead is from a taxi company that recalls dropping off the stranger outside the gate at the mansion of one of the wealthiest families in town. After Jesse survives a hail of gunfire on his home, he wonders if it could be related to the mysterious murder. When both Molly Crane and Suitcase Simpson also become targets, it's clear someone has an ax to grind against the entire Paradise Police Department. -- adapted from back cover